Effect of positive end-expiratory pressure value on change in end-tidal carbon dioxide as a predictor of fluid responsiveness in Patients Undergoing Passive Leg Raising Maneuver - Lutfi Nur Farid; Hardiono Hardiono; Pesta Parulian Maurid Edwar (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
Abstract  Identification of patients’ fluid status in the emergency room should be made before giving fluid therapy. This study aimed to determine the effect of positive end-expiratory pressure on change in end-tidal carbon dioxide during passive leg raising maneuver to predict fluid responsiveness. Thirty subjects aged 18-65 years in the resuscitation room, all on the ventilator, were divided into three groups according to their positive end-expiratory pressure value: low (0-5 cmH2O), moderate (6-10 cmH2O), and high (>10 cmH2O). Every subject underwent passive leg raising to simulate fluid administration. Values of blood pressure, heart rate, cardiac output, and end-tidal carbon dioxide were recorded before and after the maneuver. Analysis of the three groups found a significant correlation between change in end-tidal carbon dioxide with a cut-off value of 5% and 1 mmHg with fluid responsiveness of subjects in the low (p = 0.028) and moderate (p = 0.013) but not in the high positive end-expiratory pressure group (p = 0.333). In conclusion, change in end-tidal carbon dioxide in mechanically ventilated patients undergoing passive leg raising maneuvers can be used as a predictor of fluid responsiveness, but this method cannot be used on patients with high positive end-expiratory pressure (> 10 cmH2O) Keywords             : change in end tidal carbon dioxide, fluid responsiveness, positive end-expiratory pressure, passive leg raising, cardiac output surrogateCorrespondence   : lutfithe13th@gmail.com